2015
DOI: 10.3382/ps/pev124
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus amyloliquefaciens supplementation alleviates immunological stress in lipopolysaccharide-challenged broilers at early age

Abstract: This study was conducted to investigate the effect of Bacillus amyloliquefaciens ( BA: ) on the immune function of broilers challenged with lipopolysaccharide ( LPS: ). 192 one-day-old male Arbor Acre broiler chickens were randomly distributed into four treatments: 1) broilers fed a basal diet; 2) broilers fed a basal diet supplemented with BA; 3) LPS-challenged broilers fed a basal diet; and 4) LPS-challenged broilers fed a basal diet supplemented with BA. Each treatment consisted of six replicates with eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 46 publications
8
63
0
Order By: Relevance
“…Indeed, several studies have reported that the pigs fed diets supplemented with L -Met had no differences in growth performance when compared with the pigs fed with DL -Met-supplemented diets (Chen, Piao, Zhao, & Zeng, 2013;Chung & Baker, 1992;Htoo & Morales, 2016;Kong et al, 2016;Tian, Zeng, Zhang, Long, & Piao, 2016 (Han et al, 2013;Wang et al, 2005;Xu, Mellor, Birtles, Reynolds, & Simpson, 1994). Shorter villus can lead to poor nutrient absorption, resulting in a lower utilization of nutrients (Li et al, 2015). In addition, circulating DAO activity is a useful indicator of intestinal permeability and mucosal injury (Li, Lu, Hu, Sun, & Yao, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported that the pigs fed diets supplemented with L -Met had no differences in growth performance when compared with the pigs fed with DL -Met-supplemented diets (Chen, Piao, Zhao, & Zeng, 2013;Chung & Baker, 1992;Htoo & Morales, 2016;Kong et al, 2016;Tian, Zeng, Zhang, Long, & Piao, 2016 (Han et al, 2013;Wang et al, 2005;Xu, Mellor, Birtles, Reynolds, & Simpson, 1994). Shorter villus can lead to poor nutrient absorption, resulting in a lower utilization of nutrients (Li et al, 2015). In addition, circulating DAO activity is a useful indicator of intestinal permeability and mucosal injury (Li, Lu, Hu, Sun, & Yao, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial lipopolysaccharide (LPS), a complex glycolipid, is the major component of the outer surface membrane in almost all gram-negative bacteria, and it can trigger inflammatory responses in diverse eukaryotic species ranging from insects to humans by activating signal pathways and promoting gene expressions, which are involved in the regulation of immune system and inflammation (1,2) . In broiler chickens, an enormous amount of research has shown that immunological stress mimicked by administrating LPS intraperitoneally or intravenously could induce acute inflammatory responses, stimulate synthesis of pro-inflammatory cytokines and impair nutrient adsorption, which ultimately contribute to compromised growth performance of LPS-challenged broilers (3)(4)(5)(6)(7)(8) . Aside from inducing inflammation, LPS challenge would also damage intestinal barrier function (9) , a key factor associated with intestinal and body's health maintenance (10) .…”
mentioning
confidence: 99%
“…In this study, we found that the concentrations of lymphocytes and leucocytes increased significantly in the blood after intraperitoneal injection of LPS, suggesting that an immune stress response occurred after LPS challenge. Similarly, Li et al (2015) observed that LPS challenge increased the numbers of leucocytes in the whole blood of broilers.…”
Section: Itemmentioning
confidence: 80%